2020
DOI: 10.1111/mcn.13109
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and the origins of health: Interdisciplinary perspectives and priorities

Abstract: Breastfeeding and human milk (HM) are critically important to maternal, infant and population health. This paper summarizes the proceedings of a workshop that convened a multidisciplinary panel of researchers to identify key priorities and Abbreviations: HM, human milk; DHM, donor human milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 108 publications
(155 reference statements)
0
41
0
3
Order By: Relevance
“…Furthermore, heterogeneity, lack of standardisation of sample collection and processing within and between studies is a known challenge in breast milk research (64)(65)(66). The studies included in this review were no exception and, like others before us, we identified a need for greater standardisation and clearer reporting of sample collection and processing methods which we discuss below (64,66). Looking beyond the methodological limitations and challenges, we first discuss the current state of knowledge regarding the general miRNA profile in human milk, their stability and function and factors which affect them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, heterogeneity, lack of standardisation of sample collection and processing within and between studies is a known challenge in breast milk research (64)(65)(66). The studies included in this review were no exception and, like others before us, we identified a need for greater standardisation and clearer reporting of sample collection and processing methods which we discuss below (64,66). Looking beyond the methodological limitations and challenges, we first discuss the current state of knowledge regarding the general miRNA profile in human milk, their stability and function and factors which affect them.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity, lack of standardisation of sample collection and processing within and between studies is a common challenge in breast milk research (64)(65)(66). The studies included in this review were no exception and, like others before us, we identified a need for greater standardisation and clearer reporting of sample collection and processing methods (64,66). There is currently insufficient evidence to determine if it is particularly important to standardise certain aspects of the collection and processing procedures when analysing ncRNAs, such as the time of day for collection, volume of milk, or the speed and duration of centrifugation.…”
Section: Methodological Considerations Within Studiesmentioning
confidence: 99%
“…Targeted validation and absolute quantification, however, are warranted to test ’omics-derived hypotheses to generate biologically robust evidence. Well-designed studies and experiments (e.g., longitudinal sampling and a randomized controlled dose–response trial), along with a well-characterized population (e.g., metadata on maternal and infant nutrition and health and other key factors that influence milk composition) ( 94 ) and focused hypotheses to address key biological questions, are important next steps. In addition, the use of standard operating procedures as well as cross-laboratory and cross-platform validations would enhance reproducibility.…”
Section: Advances and Technologies For Human-milk Analysismentioning
confidence: 99%
“…Together, the data from our current study and our qualitative work suggest that a demand exists for skilled breastfeeding support among vulnerable women and that such services can be delivered through a CPNP site. Further research using implementation science approaches is needed to understand the feasibility and appropriateness of the integration of postnatal lactation support within CPNP sites [46]. The current context of the CPNP creates a foundation for supporting breastfeeding initiation among vulnerable women by providing an established social support structure, links to multiple community services to reduce life stresses and strong prenatal breastfeeding promotion.…”
Section: Discussionmentioning
confidence: 99%